2020
DOI: 10.1038/s41598-020-57967-y
|View full text |Cite
|
Sign up to set email alerts
|

Variation in chemokines plasma concentrations in primary care depressed patients associated with Internet-based cognitive-behavioral therapy

Abstract: How the presence of inflammation has repercussions for brain function is a topic of active research into depression. Signals released from immune system-related cells, including chemokines, might be indicative of active depression and can, hypothetically, serve as biomarkers of response to interventions, both pharmacological and psychological. The objective of this study is to analyze the peripheral plasma concentrations of CXCL12, CCL11, CX3CL1 and CCL2 in a cohort of depressed primary-care patients, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
(58 reference statements)
3
10
0
Order By: Relevance
“…Increased level of fractalkine may, therefore, constitute an independent factor associated with restrictive type of AN. Such conclusion corresponds with the data indicating that higher serum fractalkine is linked with an augmented sensitivity towards stressful stimuli and may negatively affect the mood [ 16 , 52 , 53 ]. A relatively low sensitivity of fractalkine assay used here is a limitation of the study; however, we were able to detect the compound in all but three patients’ samples.…”
Section: Discussionsupporting
confidence: 89%
“…Increased level of fractalkine may, therefore, constitute an independent factor associated with restrictive type of AN. Such conclusion corresponds with the data indicating that higher serum fractalkine is linked with an augmented sensitivity towards stressful stimuli and may negatively affect the mood [ 16 , 52 , 53 ]. A relatively low sensitivity of fractalkine assay used here is a limitation of the study; however, we were able to detect the compound in all but three patients’ samples.…”
Section: Discussionsupporting
confidence: 89%
“…Psychiatric symptoms might be related to viral-induced neuroinflammation. In this regard, persisting changes in chemokines have been detected in both, mild depression 41 and convalescent Covid patients 42 . Finally, decreased quality of life was reported by 57% of these patients 37 .…”
Section: Introductionmentioning
confidence: 86%
“…Moreover, several clinical studies found correlations between elevated levels of circulating inflammatory chemokines and depressive symptoms in patients with major depressive disorder [73,[80][81][82][83]. According to the results of a comprehensive meta-analysis, peripheral concentrations of a number of chemokines including CCL2, CCL3, CCL4, CCL11, CXCL4, CXCL7, and CXCL8 can potentially discriminate between individuals with depression and those without [84].…”
Section: Brief Overview Of Chemokines and Their Role In Depressionmentioning
confidence: 99%